2023
DOI: 10.3390/en16166074
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Global Greenhouse Gas Emissions in Human Deaths to Guide Energy Policy

Joshua M. Pearce,
Richard Parncutt

Abstract: When attempting to quantify future harms caused by carbon emissions and to set appropriate energy policies, it has been argued that the most important metric is the number of human deaths caused by climate change. Several studies have attempted to overcome the uncertainties associated with such forecasting. In this article, approaches to estimating future human death tolls from climate change relevant at any scale or location are compared and synthesized, and implications for energy policy are considered. Seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…Global climate change, caused by greenhouse gas emissions from conventional power generation from coal, natural gas, and oil, contributing 18%, 40%, and 1% to global electricity production in 2022, poses a concern [1]. This increases negative impacts on human health [2][3][4], reduces agricultural productivity [5], and has economic [6][7][8] consequences. One approach to eliminating the need for fossil fuel electric generation is to replace it with renewable sources to address these challenges [9].…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change, caused by greenhouse gas emissions from conventional power generation from coal, natural gas, and oil, contributing 18%, 40%, and 1% to global electricity production in 2022, poses a concern [1]. This increases negative impacts on human health [2][3][4], reduces agricultural productivity [5], and has economic [6][7][8] consequences. One approach to eliminating the need for fossil fuel electric generation is to replace it with renewable sources to address these challenges [9].…”
Section: Introductionmentioning
confidence: 99%
“…(Arent et al, 2014, p. 662) After summarizing the peer-reviewed economic literature, the 2022 IPCC Report concluded that: "warming of ~4°C may cause a 10-23% decline in annual global GDP by 2100 relative to global GDP without warming." (IPCC 2022, p. 2459) In contrast, Pearce and Parncutt (2023) argue that global warming of even 2 °C will kill approximately 1 billion (mainly poorer) humans, and many climate scientists argue that the impact of even a 3°C increase could be "catastrophic" (e.g., .…”
Section: Introductionmentioning
confidence: 99%
“…(Arent et al, 2014, p. 662) After summarizing the peer-reviewed economic literature, the 2022 IPCC Report concluded that: "warming of ~4°C may cause a 10-23% decline in annual global GDP by 2100 relative to global GDP without warming." (IPCC , p. 2459 In contrast, Pearce and Parncutt (2023) argue that global warming of even 2 °C will kill approximately 1 billion (mainly poorer) humans, and many climate scientists argue that the impact of even a 3°C increase could be "catastrophic" (e.g., .…”
Section: Introductionmentioning
confidence: 99%